RAGAM HIAS ULOS SADUM MANDAILING - Juliana, Netty (JURNAL KELUARGA SEHAT SEJAHTERA, 2015)
ABSTRACT   Ornament is a two-dimensional form which has length and width of more than one side of the meet and face to face with the results in a form of manifestation. Besides decoration has more than one side, decoration is inseparable from the form of color. Thus ornament is inseparable from the form or shape of two-dimensional and color in composition form. Social environment and for nature around always affect the form of decoration. So the form of decoration with the different decorative of Mandailaing Batak Karo Batak can be observed from the results of the traditional craft Ulos Sadum. Sadum Ulos ornament consisting of flora, fauna, and natural shapes of objects. In particular decoration, Ulos Sadum Hobo mandailing consists of several forms, there are: pusuk ni robung, stylized plant corn, bona fur, jagar-jagar, volute or bondul na opat, aropik or burangir, stylized flower coffee, thick vertical lines or experience na alternating, body-soul, and stylized buffalo. Colors shown on the hobo Sadum Ulos Mandailaing consists of burgundy, black, white, yellow, and green. The combination of form and color produces ethnic decoration, and has its own characteristics. Because this Maidiling Sadum Ulos form contains the meaning and the message itself for Mandailaing Batak society. Kata Kunci : Ragam hias, Ulos.